AURIEL‐PsO: a randomized, double‐blind phase III equivalence trial to demonstrate the clinical similarity of the proposed biosimilar MSB11022 to reference adalimumab in patients with moderate‐to‐severe chronic plaque‐type psoriasis. (26th September 2019) - Hercogová, J.; Papp, K.A.; Chyrok, V.; Ullmann, M.; Vlachos, P.; Edwards, C.J.
Summary: Background: MSB11022 is a proposed adalimumab biosimilar. Objectives: To compare the efficacy, safety and immunogenicity of MSB11022 with reference adalimumab. Methods: AURIEL‐PsO was a double‐blind randomized controlled equivalence trial, in which patients with moderate‐to‐severe chronic plaque‐type psoriasis were randomized 1 : 1 to MSB11022 or reference adalimumab. The primary end point was ≥ 75% improvement in Psoriasis Area and Severity Index (PASI 75) at week 16, with a prespecified equivalence interval of ± 18%. Patients with a ≥50% improvement in PASI at week 16 were eligible to enter a double‐blind extension period: patients receiving MSB11022 continued treatment, and patients receiving reference adalimumab were rerandomized 1 : 1 either to continue reference adalimumab or to switch to MSB11022. Other efficacy end points and safety, immunogenicity and pharmacokinetic parameters were evaluated at scheduled visits up to weeks 52 (efficacy and immunogenicity), 54 and 66 (safety). Results: In total, 443 patients were randomized. The difference in PASI 75 response rates at week 16 between the treatment arms was −1·9%, and the 95% confidence interval (−7·8% to 4·1%) was within the prespecified equivalence interval. No notable difference in the incidence of treatment‐emergent adverse events was observed between treatment arms up to the end of the trial, and no new safety signals were observed. Following treatment switch at week 16, no clinically meaningful differences in safety or immunogenicity were seen between treatment arms through to the end of the observation period. Conclusions: Therapeutic equivalence between MSB11022 and reference adalimumab was demonstrated. AURIEL‐PsO provides evidence to support the similarity of both products with regard to efficacy, safety and immunogenicity. What's already known about this topic? Adalimumab is a fully human antitumour necrosis factor‐α monoclonal antibody, indicated for the treatment of multiple inflammatory disorders, including psoriasis, psoriatic arthritis, rheumatoid arthritis, inflammatory bowel diseases and ankylosing spondylitis. MSB11022 is a proposed adalimumab biosimilar that has shown structural and functional similarity to the reference product in an extensive analytical comparability exercise. MSB11022 has demonstrated bioequivalence and comparable safety and immunogenicity profiles in a phase I study in healthy volunteers. What does this study add? This phase III study confirmed equivalent efficacy for MSB11022 and reference adalimumab in patients without any immunomodulation comedication in moderate‐to‐severe chronic plaque‐type psoriasis at week 16. The efficacy, safety and immunogenicity of MSB11022 and reference adalimumab were similar over the respective observation periods (week 52 for efficacy and immunogenicity, week 66 for safety). A switch from reference adalimumab to MSB11022 at week 16 did not impact efficacy, safety or immunogenicity. Abstract : Linked Comment: Borroni and Costanzo. Br J Dermatol 2020; 182 :266 .